Role of PET/CT in the follow-up of postoperative and/or post-therapy cancer rectum: comparison with pelvic MRI - Mohamed H. Faheem; Evram Nathan; Ahmed Farid Youssef (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background In locally advanced rectal cancer, many imaging modalities are used, for example 18F-2-fluoro-2-deoxy-d-glucose (18F-FDG) positron emission tomography-computed tomography (PET-CT) and MRI. The aim of our study is to compare the diagnostic accuracy of 18 F-FDG-PET/CT & pelvic MRI; as well as to investigate the possible added value of using combined pelvic MRI and PET-CT for assessment of tumor response. Results Regarding the presence of local tumor, both PET CT and MRI showed perfect agreement with 97.1% overall accuracy, while in N category, PET CT showed higher specificity but lower sensitivity than MRI. MRI was superior to PET/CT in detecting extension to nearby organs; owing to the more anatomical details of MRI regarding the involvement of mesorectal fascia and EMVI. Almost total agreement of both MRI and PET/CT was noticed in evaluating post-therapy and postoperative complications. Conclusion For locally advanced rectal cancer (pT3–4 N0 M0 or any T N1 M0), a multimodality strategy has been shown to be the best option to evaluate local disease process, using the diagnostic criteria that were based on morphology, as well as glucose uptake, instead of the SUV alone for reassessment of post-therapy or postoperative changes.